Solon of Athens : new historical and philological approaches - Blok, Josine.; Lardinois, A. P. M. H. (Mnemosyne, Supplements, 2006)
This volume offers a range of innovative approaches to Solon of Athens, legendary law-giver, statesman, and poet of the early sixth century B.C. In the first part, Solon's poetry is reconsidered against the background of oral poetics and other early Greek poetry. The connection between Solon's alleged roles as poet and as politician is fundamentally questioned. Part two offers a reassessment of Solon's laws based on a revision of the textual tradition and recent views on early Greek lawgiving. In part three, fresh scrutiny of the archeological and written evidence of archaic Greece results in new perspectives on the agricultural crisis and Solon's role in the social and political developments of sixth-century Athens. Originally published in hardcover